Closing the Deal: A Cross-Cultural Comparison of Treatment Resistance. Issue 11 (2nd November 2018) - Bergen, Clara; Stivers, Tanya; Barnes, Rebecca K.; Heritage, John; McCabe, Rose; Thompson, Laura; Toerien, Merran
ABSTRACT: This study investigates patient resistance to doctors' treatment recommendations in a cross-national comparison of primary care. Through this lens, we explore English and American patients' enacted priorities, expectations, and assumptions about treating routine illnesses with prescription versus over-the-counter medications. We perform a detailed analysis of 304 (American) and 393 (English) naturally occurring treatment discussions and conclude that American and English patients tend to use treatment resistance in different prescribing contexts to pursue different ends. While American patients are most likely to resist recommendations for non-prescription treatment and display an expectation for prescription treatment in these interactions, English patients show a high level of resistance to recommendations for all types of treatment and display an expectation of cautious prescribing. These behavioral trends reflect broader structural forces unique to each national context and ultimately maintain distinct cultural norms of good-practice prescribing.